Illustrated Books as Information Media for Pranata Mangsa (Old Javanese Astrology) - Wantoro; Febby Permata Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is an explanation of the design of illustration book media which aims to introduce Pranata Mangsa as one of Indonesian culture. Pranata Mangsa is a calendar system related to agricultural activities, especially for farming or fishing in Javanese society. Unfortunately, Pranata Mangsa is now less well known by the public because of changes in human lifestyles that affect mindsets and behavior patterns. Sophisticated technology can make it easier for humans, reducing the use of things about values, customs, and ancestral traditions. In this design, two methods are used, namely communication strategies and creative strategies. Communication strategies and creative strategies in this design are used to present and provide ideas and concepts that can make the public interested in Pranata Mangsa information media. The expected impact of this design is an increased sense of community awareness and participation in appreciating the cultural diversity of Indonesia.